The Complex Alarming Event Detecting and Disposal Processing Approach for Coal Mine Safety Using Wireless Sensor Network. (29th November 2012) - Bo, Cheng; Peng, Zhou; Da, Zhu; Junliang, Chen
Abstract : Due to the complex environment of the coal mine, the accidents can occur at any time and often result in partial or total evacuation of mine personnel and could result in the loss of lives. Therefore, it is important and necessary to detect the accidents and generate a corresponding alarming disposal in time. This paper proposed a real-time complex alarming event detecting and disposal processing approach for coal mine safety using wireless sensor network. Firstly, we introduce the event and complex events model, offer fully customizable policies for event selection and consumption, and also describe the state-automata-based complex event detection algorithm. Then, we describe an event-driven service coordination pattern for the behavioral model, which is based on event-condition-action triggering with BPEL control flow realized using decoupled publish/subscribe semantics. Finally, the system implementation is presented and deployed in the coal mine, showing the effectiveness of the proposed approach.